Harnessing Extrinsic Dissipation to Enhance the Toughness of Composites and Composite Joints A State-of-the-Art Review of Recent Advances - Lubineau, Gilles (Advanced materials (Deerfield Beach, Fla.), 2024)
© 2024 The Author(s). Advanced Materials published by Wiley‐VCH GmbH.